2020
DOI: 10.1021/acs.jpclett.0c00206
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Dynamics and Electron–Phonon Coupling in Lead-Free Cs2AgIn1–xBixCl6 Double Perovskite Nanocrystals

Abstract: Recently, lead free all-inorganic double perovskites have revolutionized photovoltaic research, showing promising light emitting efficiency and tunability via modification of inherent structural and chemical properties. Here, we report a combined experimental and theoretical study on the variation of carrier–lattice interaction and optoelectronic properties of Cs2AgIn1–x Bi x Cl6 double perovskite nanocrystals with varying alloying concentrations. Our UV–vis study confirms the parity allowed first direct trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 54 publications
16
71
0
Order By: Relevance
“…[ 151 ] Work by Manna et al. [ 152 ] combined Raman measurements with density functional theory (DFT) calculations, finding Fröhlich coupling constants in the range α F = 2−5 for Cs 2 AgIn 1− x Bi x Cl 6 nanocrystals, and calculations of charge‐carrier mobilities using the Feynman/Hellwarth polaron model suggested upper limits of 2−52 cm 2 V −1 s −1 in nanocrystals across the range of x . [ 152 ]…”
Section: Polarons In Metal‐halide Semiconductorsmentioning
confidence: 99%
“…[ 151 ] Work by Manna et al. [ 152 ] combined Raman measurements with density functional theory (DFT) calculations, finding Fröhlich coupling constants in the range α F = 2−5 for Cs 2 AgIn 1− x Bi x Cl 6 nanocrystals, and calculations of charge‐carrier mobilities using the Feynman/Hellwarth polaron model suggested upper limits of 2−52 cm 2 V −1 s −1 in nanocrystals across the range of x . [ 152 ]…”
Section: Polarons In Metal‐halide Semiconductorsmentioning
confidence: 99%
“…[ 143,144 ] The aforementioned theoretical analysis gives us a chance to tune the bandgap of HDPs through precise component engineering and unexpected optoelectronic properties will be uncovered. [ 68,145–147 ]…”
Section: Optical Properties Of Hdpsmentioning
confidence: 99%
“…(b) Reproduced with permission. [ 145 ] Copyright 2017, American Chemical Society. (c) Reproduced with permission.…”
Section: Optical Properties Of Hdpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Manna et al. [ 150 ] studied the band structure of Bi 3+ doped Cs 2 AgInCl 6 nanocrystals in detail. They observed that the width of bandgap reduced and the VBM composed of hybridization between the Ag 4d and Cl 3p transformed into Bi 6p orbital with increasing substitution ratio of Bi 3+ (Figure 8c).…”
Section: Strategies For Boosting the Efficiency Of Halide Double Peromentioning
confidence: 99%